Objektivikasi Perempuan dalam Tiga Dongeng Klasik Indonesia dari Sanggar Tumpal: Sangkuriang, Jaka Tarub, dan Si Leungli - Hapsarani, Dhita (UI Scholars Hub, 2017)
Research on gender representation in folk tales has shown that oftentimes values embedded in folk tales are not in line with contemporary gender values. This paper aims at revealing the objectification of women in three Indonesian folktales turned into children’s literature, which are Si Leungli, Jaka Tarub, and Sangkuriang rewritten by a group of writers and illustrators under the name Sanggar Tumpal. The research uses Nussbaum and Langton’s concept on objectification to analyze the text and the illustrations. The result of the research shows that both the text and the pictures of the three books display consistent portrayal of women being the objects of male desire, domination and violence indicating an endorsement of the normality of such practices.